Responsive Neurostimulation of the Thalamus Improves Seizure Control in Idiopathic Generalized Epilepsy: A Case Report. Issue 5 (November 2020) - Kokkinos, Vasileios; Urban, Alexandra; Sisterson, Nathaniel D; Li, Ningfei; Corson, Danielle; Richardson, Mark R
Abstract : BACKGROUND AND IMPORTANCE: : At least 25% of patients with idiopathic generalized epilepsy do not obtain adequate seizure control with medication. This report describes the first use of responsive neurostimulation (RNS), bilaterally targeting the centromedian/ventrolateral (CM/VL) region in a patient with drug‐refractory Jeavons syndrome (eyelid myoclonia with absences). CLINICAL PRESENTATION: : A patient, diagnosed with eyelid myoclonia with absences (EMA) and refractory to medication, was offered RNS treatment in the CM/VL region of the thalamus. Stimulation was triggered by thalamic neural activity having morphological, spectral, and synchronous features that corresponded to 3‐ to 5‐Hz spike‐wave discharges recorded on prior scalp electroencephalography. CONCLUSION: : RNS decreased daily absence seizures from a mean of 60 to ≤10 and maintained the patient's level of consciousness during the occurring episodes. This therapy should be evaluated further for its potential to treat patients with pharmaco‐refractory generalized epilepsy.